Chronicles of a Two-Front War : Civil Rights and Vietnam in the African American Press - Eldridge, Lawrence Allen, 1937- (Book collections on Project MUSE., 2011)
During the Vietnam War, young African Americans fought to protect the freedoms of Southeast Asians and died in disproportionate numbers compared to their white counterparts. Despite their sacrifices, black Americans were unable to secure equal rights at home, and because the importance of the war overshadowed the civil rights movement in the minds of politicians and the public, it seemed that further progress might never come. For many African Americans, the bloodshed, loss, and disappointment of war became just another chapter in the history of the civil rights movement. Lawrence Allen Eldridge explores this two-front war, showing how the African American press grappled with the Vietnam War and its impact on the struggle for civil rights. This book is the first to examine coverage of the Vietnam War by black news publications, from the Gulf of Tonkin incident in August 1964 to the final withdrawal of American ground forces in the spring of 1973 and the fall of Saigon in the spring of 1975. Eldridge reveals how the black press not only reported the war but also weighed its significance in the context of the civil rights movement. In analyzing seventeen African American newspapers, the author examines not only the role of reporters during the war, but also those of editors, commentators, and cartoonists. Especially enlightening is the research drawn from extensive oral histories by prominent journalist Ethel Payne, the first African American woman to receive the title of war correspondent. She described a widespread practice in black papers of reworking material from major white papers without providing proper credit, as the demand for news swamped the small budgets and limited staffs of African American papers. The author analyzes both the strengths of the black print media and the weaknesses in their coverage. He augmented this study with a rich array of primary sources--including interviews with black journalists and editors, oral history collections, the personal papers of key figures in the black press, and government documents, including those from the presidential libraries of Lyndon Johnson, Richard Nixon, and Gerald Ford--to trace the ups and downs of U.S. domestic and wartime policy especially as it related to the impact of the war on civil rights. The black press ultimately viewed the Vietnam War through the lens of African American experience, blaming the war for crippling LBJ's Great Society and the War on Poverty. Despite its waning hopes for an improved life, the black press soldiered on.